Legal Problems of Energy Dependence of the EU and its Members on Russia as a Background for the Disintegration of the EU - Konaszczuk, Wojciech (PRAWO i WIĘŹ, 2024)
The main thesis of this paper is aimed at the conclusion that currently the EU, as an international organization, will not be able to ensure the energy security of its member states in the next ten years. The second thesis, as a consequence of demonstrating the validity of the first thesis, is related to the system of human rights protection in the EU, according to which every EU citizen has the right to an adequate standard of living. One of the basic elements of an adequate standard of living is to ensure the right of EU residents to have access to energy sources at a price acceptable to them. In conclusion, it will be shown that the EU and the Member State governments are not in a position to guarantee a sense of energy security for citizens and all sectors of the economy. The study is divided into two periods. The first period is up to the start of the armed conflict in February 2022. The second period under study, on the other hand, begins after Russia invades Ukrainian territory.